Optimization of Fe2+ supplement in anaerobic digestion accounting for the Fe-bioavailability. (February 2018) - Cai, Yafan; Zhao, Xiaoling; Zhao, Yubin; Wang, Hongliang; Yuan, Xufeng; Zhu, Wanbin; Cui, Zongjun; Wang, Xiaofen
Graphical abstract: Highlights: Anaerobic digestion of rice straw was investigated. It is accelerated under appropriate levels of Fe trace elements. The bioavailability of Fe is low and varies within a narrow range (1.7–3.1 wt%). An appropriate amount of Fe 2+ enhances the hydrolysis efficiency of rice straw. An appropriate amount of Fe 2+ provides an easier metabolic environment. Abstract: Fe is widely used as an additive in anaerobic digestion, but its bioavailability and the mechanism by which it enhances digestion are unclear. In this study, sequential extraction was used to measure Fe bioavailability, while biochemical parameters, kinetics model and Q-PCR (fluorescence quantitative PCR) were used to explore its mechanism of stimulation. The results showed that sequential extraction is a suitable method to assess the anaerobic system bioavailability of Fe, which is low and fluctuates to a limited extent (1.7 to –3.1 wt%), indicating that it would be easy for Fe levels to be insufficient. Methane yield increased when the added Fe 2+ was 10–500 mg/L. Appropriate amounts of Fe 2+ accelerated the decomposition of rice straw and facilitated methanogen metabolism, thereby improving reactor performance. The modified Gompertz model better fitted the results than the first-order kinetic model. Feasibility analysis showed that addition of Fe 2+ at ≤50 mg/L was suitable.